PARADOKS PENETAPAN USIA PERKAWINAN DALAM UNDANG-UNDANG PERKAWINAN SECARA HUKUM NORMATIF - Khoiruddin Manahan Siregar (Yurisprudentia: Jurnal Hukum Ekonomi, 2019)
Marriage  is  a  bond  between  two  human  beings  in  their  lives  which  is  very important.  Once  the  importance  of  marriage,  it  is  not  surprising  that  the  world's religions regulate marriage, even the customs of society and state institutions do not lag behind regulating the marriage that prevails among the people.  The  law  regulates  marriages,  one  of  which  is  the  minimum  age  of  marriage contained in article 7 paragraph (1) which states that, "Marriage is only permitted if the male has reached the age of 19 (nineteen) years and the woman has reached the age of 16 (sixteen) ) year ".